Analisis Implementasi Elemen Interior di SLB-B YRTRW Surakarta Berdasarkan Konsep Deaf Space - Anna Pratista Andanitya (Arsir: Jurnal Arsitektur, 2024)
The Extraordinary School for Rehabilitation of Deaf and Speech Impaired Foundation (YRTRW) is one of the educational foundations for deaf children in Surakarta. There is lack of ideal needs for deaf children when using public facilities in terms of comfort and safety, so this is a consideration in developing public facilities. In particular, the educational facilities for deaf children in Surakarta are not entirely ideal due to the limited benefits and functions of the spatial elements. It is because some problem factors that are typical of deaf people need to be connected in the development of interior elements to furnish the right solution for deaf people to be able to perform activities optimally and independently. This research was conducted to review the design of interior elements in the SLB-B YRTRW Surakarta. This research uses the qualitative descriptive method and is collected through observations, interviews, documentation, and analysis using literature study. The results of this study showed shortcomings in the interior design of the SLB-B YRTRW Surakarta reanalyzed in the 5 principles of The Deaf Space Design Guidelines by Hansel Bauman. Three principles have not been met: space and proximity, sensory reach, and mobility and proximity.